Islamic Legal Justice and The Challenges of International Trade Liberalization - Roy, Royani; Mahmud, Mahmud; Rosadi, Aden; Setiawan, Iwan (UPT Publikasi Ilmiah UNISBA, 2025)
International trade liberalization creates significant structural imbalances in Muslim-majority countries, primarily evident in the unequal distribution of trade benefits and the exploitation of resources. The key problem is the lack of an evaluation framework that combines Islamic justice principles (‘adl) with modern trade data to measure how liberalization policies impact Muslim communities. This study examines the compatibility of international trade liberalization with Islamic economic values and develops a practical evaluation model for the design of trade policies in Muslim countries. Unlike earlier studies, it creates a new analytical framework that integrates the three dimensions of justice in Islam (distributive, procedural, and corrective justice) with current trade indicators, using a qualitative approach and systematic literature review, supplemented with contemporary Islamic interpretations of trade in the Quran and hadith. The research introduces the